Chryseobacterium potabilaquae sp. nov., Chryseobacterium aquaeductus sp. nov. and Chryseobacterium fistulae sp. nov., from drinking water systems. Issue 9 (27th September 2021) - Lucena, Teresa; Ruvira, María A.; Macián, M. Carmen; Arahal, David R.; Aznar, Rosa; Pujalte, María J.
Abstract : A polyphasic taxonomic study was conducted on three strains isolated from drinking water systems that had previously been deposited as Chryseobacterium species at the Spanish Type Culture Collection in order to complete their classification. Strains CECT 9293 T, CECT 9390 T and CECT 9393 T were isolated from sites in Barcelona, Spain, in the framework of a project aimed at generating the first MALDI-TOF database specific for bacteria present in water for human consumption. Their partial 16S rRNA sequences showed that their closest relatives among the type strains of Chryseobacterium exhibited 98 % similarity or less, supporting their taxonomic novelty. At the same time, comparison between them revealed that strains CECT 9293 T and CECT 9393 T could perhaps be related at the species level as they shared 99.5 % similarity. However, whole genome sequencing was performed and the subsequent calculation of relatedness indices, average nucleotide identity and estimated DNA–DNA hybridization, ruled out that possibility and confirmed instead that each of the strains should be considered a separate species in the genus Chryseobacterium . Having clarified their status, we also performed phylogenomic analyses and searched for possible environmental or non-type material sequences that could be related to any of them at the species level. In parallel, the strains were characterized phenotypically and compared to their closest relatives to determine diagnostic traits to support their formal proposal. The proposed species are Chryseobacterium potabilaquae sp. nov. with the type strain CECT 9293 T (=LMG 32084 T ), Chryseobacterium aquaeductus sp. nov. with the type strain CECT 9390 T (=LMG 32085 T ) and Chryseobacterium fistulae sp. nov. with the type strain CECT 9393 T (=LMG 32086 T ).